Vulnerabilidade social do município de Curimatã, Piauí: estudo de caso das comunidades atendidas pelo Programa "Água Pura Para Crianças" - Ferreira, Michel Monteiro (2024)
The problem triggered by water scarcity in the Brazilian semi-arid region is not limited to the lack of water, but to precarious access to the quantity and quality of the available resource, resulting from negligence in public basic sanitation policies. This gap is a growing concern, as it directly affects the quality of life and health of communities, especially in rural areas. The study aims to analyze the levels of social vulnerability in Curimatá-Piauí and examine the impact of the “Pure Water for Children Program” on accessibility to water and basic sanitation. To achieve this goal, a municipal Social Vulnerability Index (IVS) was created, divided into three dimensions: Household Infrastructure, Income and Socioeconomic Situation, using data from the 2010 IBGE Demographic Census. In addition, a case study of ex-ante and ex-post evaluation was carried out in seven communities affected by water scarcity. This study involved documentary analysis and the use of Geographic Information System (GIS) tools to spatialize the data, allowing for a more comprehensive understanding of the local reality. Analysis of the data from 2010 and the case study carried out between 2020 and 2023 revealed little change in social vulnerability in terms of access to water and sanitation in the municipality. The results highlight that, despite advances in the sanitation sector, rural areas continue to face significant challenges, with scarce investments and persistent problems of access to drinking water and basic sanitation. The communities of Baio (census tract 12) and Lagoa Verde (census tract 19) stood out as having critical conditions in the indicators analyzed in the SVI and case study. In addition, the research shows that urban areas face similar problems. This condition reflects the importance of basic sanitation as a fundamental condition for promoting community health and contributing to environmental protection. As well as recognizing the fundamental role of Civil Society Organizations in contributing to reducing social vulnerability and improving the living conditions of marginalized communities. It is hoped that the results of this study will support public authorities in better managing public investments in Curimatá, addressing the weaknesses identified in the census sectors (communities) and contributing to significant improvements in the population's quality of life.